ASSOCIATION OF FAMILYâS SUPPORT, ATTITUDE AND BEHAVIOR TO QUALITY OF LIFE OF PATIENT WITH DIABETES MELLITUS TYPE II - Metasari, Sherly (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: As diabetes mellitus has become the global burden of disease, regional center Endocrinology Society of West Kalimantan found the prevalence of DM was quite high, at 11%. Lack of support, attitudes and family roles to patients with Diabetes Mellitus type II were found as the determinant factors of low quality life of patients with DM type II. Aims: to assess the association of familyâs support, attitudes and behaviors with the quality of life of patients with diabetes mellitus type II Methods: This research was a quantitative research using correlation analytic method and cross sectional approach that emphasizes time measurement / observation of independent and dependent variable data, only once at one time. In 11-day sampling, thirty (30) patients with diabetes mellitus type II were selected from total 282 patients who visited Kitamura Pontianak Clinic, Indonesia, using a non-probability sampling (non-random sample) with consecutive sampling method. A questionnaire was employed in order to assess the level of familyâs support, attitude, and behavior to quality of life of the participated patients. Results: From total 30 selected patients, only 26.7% had good support from their family. Moreover, the majority notified their family orchestrating less attitude and behavior toward Diabetes Mellitus type II, respectively, at the percentage of 40% and 46.7%. In the other hand, only 6 patients claimed their family having either good attitude or good behavior. It is not surprising notice only 20 respondents claimed they had good quality of life, while 36.7% declared having enough quality of life, and the majority (43.3%) experienced less quality of life responding to their health. Using Rank Spearmen test, the data suggests that there were significantly positive association between familyâs support, attitude, and behavior toward respondentsâ life quality, with significant value less than 0.05. Conclusions: Finding revealed among the participated patients with Diabetes Mellitus type II at Kitamura Pontianak Clinic, Indonesia, their family orchestrate low support, attitude, and behavior toward the disease. The results suggest the important role of family to the health, comfort, and happiness among the patients. Family should be active in finding information about Diabetes Mellitus, certainly in controlling blood sugar.Â